Thermal performance of thermal management system coupling composite phase change material to water cooling with double s-shaped micro-channels for prismatic lithium-ion battery. (January 2022) - Gao, Zhengyuan; Deng, Fang; Yan, Dong; Zhu, Hui; An, Zhiguo; Sun, Pengfei
Highlights: Composite phase change material coupled with water cooling. Active cooling system with double S-shaped micro-channels. Optimal parameters for a prismatic lithium-ion battery thermal management system. 20% expanded graphite doped into phase change material is more suitable. Abstract: The heat dissipation of lithium-ion batteries is very important for the safety of electric vehicles (EVs), especially at high discharge rate and ambient temperature. A novel battery thermal management system (BTMS) coupling composite phase change material (CPCM) and water cooling with double s-shaped micro-channels was proposed. To improve the thermal conductivity of the phase change material (PCM), expanded graphite (EG) was doped into the paraffin wax. The effects of the mass fraction of EG in CPCM, the liquid flow rate, the discharge rate and the ambient temperature on thermal performance for the BTMS were investigated through the numerical simulation and physical experiment. The results indicate that the thermal dissipation of the BTMS is much better than that of passive BTMS with CPCM and no heat dissipation structure. The heat dissipation effect of the BTMS with 20% EG/PCM is better than that of other mass fractions, and the maximum temperature and temperature difference of the module can be controlled to 47.338 °C and 4.8 °C, respectively. Moreover, when water flows at a lower rate in the micro-channels, increasing the water flow rate will significantly improve the thermal performance of the battery module. However, the further increase of flow rate has insignificant effect when the water flow rate is over 0.3 m.s −1 . Considering the external energy consumption and thermal performance, when the micro-channel setup is in reverse flow and the water flow rate is 0.3 m.s −1, the BTMS has the best performance. Graphic abstract: Image, graphical abstract